2000
DOI: 10.1088/0951-7715/13/3/301
|View full text |Cite
|
Sign up to set email alerts
|

A new estimate of the Hausdorff measure of the Sierpinski gasket

Abstract: In this paper, we develop the hexagon method and the dodecagon method to estimate the Hausdorff measure of the Sierpiński gasket and show that the Hausdorff measure of the Sierpiński gasket is upper-bounded by a single-variable continuous function. Better upper bounds of the Hausdorff measure of the Sierpiński gasket are also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Like the Case (1), it is easy to prove that a (5) n decreases. Suppose that lim n→∞ a (5) n = α 5 ,by…”
Section: The Hausdorff Measure Of the Sierpinski Carpetmentioning
confidence: 91%
“…Like the Case (1), it is easy to prove that a (5) n decreases. Suppose that lim n→∞ a (5) n = α 5 ,by…”
Section: The Hausdorff Measure Of the Sierpinski Carpetmentioning
confidence: 91%
“…In [4], Marion gave an upper bound for s-dimensional Hausdorff measure H s (S) of the Sierpinski gasket S, H s (S) 3 s /6 ≈ 0.9508, and conjectured that this was its actual value of Hausdorff measure. But, Zhou [5] showed that the conjecture was not true and in [7] …”
Section: The Sierpinski Gasket S Satisfies the Open Set Condition: Thmentioning
confidence: 99%
“…With the help of the principle of mass distribution, the Hausdorff measure of a Sierpinski carpet which equals 2 is obtained in [4]. The references [5] and [6] respectively gave the upper and lower bound for the Hausdorff measure of the Sierpinski gasket.…”
Section: Introductionmentioning
confidence: 99%